Dog ownership, glycaemic control and all-cause death in patients with newly diagnosed type 2 diabetes: a national cohort study - Karin Rådholm; Karin Rådholm; Peder af Geijerstam; Mark Woodward; Mark Woodward; John Chalmers; Margareta Hellgren; Margareta Hellgren; Stefan Jansson; Stefan Jansson; Olov Rolandsson (Frontiers Media S.A., 2023)
AimsTo evaluate whether dog ownership from the time of type 2 diabetes diagnosis improved glycaemic control, increased achievement of major guideline treatment goals or reduced the risk of all-cause death.MethodsPatients diagnosed with type 2 diabetes were followed by linkage of four Swedish national registers covering diabetes, dog ownership, socioeconomics, and mortality. Linear regression was used to estimate the mean yearly change in glycated haemoglobin (HbA1c). Cox survival analysis and logistic regression were used to analyse associations between dog ownership and all-cause death and achievement of treatment goals, respectively.ResultsOf 218,345 individuals included, 8,352 (3.8%) were dog-owners. Median follow-up was 5.2 years. Dog-owners had worse yearly change in HbA1c, and were less likely to reach HbA1c, low-density lipoprotein (LDL), and systolic blood pressure (SBP) treatment goals than non-dog-owners (adjusted odds ratios [95% CI] of 0.93 [0.88-0.97], 0.91 [0.86-0.95], and 0.95 [0.90-1.00], respectively). There was no difference in the risk of all-cause death (adjusted hazard ratio [95% CI] 0.92 [0.81-1.04], dog owners versus not).ConclusionOwning a dog when diagnosed with diabetes did not lead to better achievement of treatment goals or reduced mortality, but was in fact associated with a smaller reduction in HbA1c and reduced likelihood of achieving treatment goals.